Interrelationship of farmers’ knowledge, attitude, ease of use of technology, motivation and work performance in fertilizer application on rice in Bangladesh - Bagum, Thahamina (2021)
An enormous potential exists for increases in rice yield in Bangladesh. However, inefficient and imbalanced fertilizer use often impedes farmers from achieving expected yields. Farmers have resorted to applying fertilizers at inappropriate rates that do not match well with the nutrient requirement of certain crops. It is evident from past research that a majority of farmers hardly use the recommended rates for fertilizers. Therefore, this study aims to: (i) assess the level of knowledge, attitude, ease of use of technology, and motivation of farmers in fertilizer application on rice, (ii) determine the level of farmers’ work performance in fertilizer application on rice, (iii) explore the relationships between knowledge, attitude, ease of use of technology and motivation of farmers with their wok performance in fertilizer application on rice, and (iv) investigate the contribution of knowledge, attitude, ease of use of technology and motivation of farmers to their work performance in fertilizer application on rice. The work performance theory, the Ability, Motivation, and Opportunity (AMO) model, and the Technology Acceptance Model (TAM) were used to develop the theoretical foundation for this work performance study. Besides, hypotheses were developed in light of these theories and the empirical findings of previous similar studies. This research used a multistage sampling method to reach farmers from twenty one (21) rice production areas in Bangladesh. From a total of 3762 farmers, 355 rice farmers were selected using the simple random technique as sample for the study. A structured questionnaire was adapted to collect data from the respondents. A five (5) point Likert scale was used to measure the dependent as well as independent variables. Data were subjected to descriptive analysis (mean, standard deviation) to describe the level of selected variables. The Pearson correlation analysis was measured to explain the relationships between knowledge, attitude, ease of use of technology and motivation of farmers with their work performance in fertilizer application on rice. A multiple linear regression analysis was deployed to identify the highest contributing factors towards farmers’ work performance in fertilizer application on rice. Results revealed that most of the farmers sampled had a moderate level of knowledge, favorable attitude, moderate level of ease of use of technology and a moderate level of motivation in fertilizer application on rice. About 45.9% of the farmers had a high level of work performance in fertilizer application. Knowledge, attitude, ease of use of technology and motivation of farmers had significant positive relationships with their work performance in fertilizer application on rice. Moreover, knowledge and motivation were found to be strongly related to farmers’ work performance in fertilizer application, while ease of use of technology and attitude showed moderate and low relationship, respectively. The multiple linear regression analysis showed that knowledge, ease of use of technology and motivation of farmers significantly contributed to their work performance, while attitude insignificantly contributed to their work performance in fertilizer application. All the variables explained 56.1% of the variance in farmers’ work performance in fertilizer application on rice. Motivation of farmers was found to be the highest contributing factor followed by knowledge and ease of use of technology influencing farmers’ work performance in fertilizer application on rice. Since majority of the farmers had a high level of work performance, the study concludes that there is still ample scope to improve the rest of farmers’ work performance in fertilizer application to attain higher production of rice. Besides, knowledge, ease of use of technology, and motivation of farmers were found significant to their work performance. Therefore, these factors should be paid greater attention to improve the farmers’ work performance in fertilizer application. The study recommended that the findings could be used as a reference for similar research in future. Moreover, the study findings will serve as a basis for formulating essential policies and procedures for field extension, supervision, guidance, counselling and training of farmers. This will in turn help inspire and ensure improvements in work performance, specifically towards the application of fertilizer on rice among other farmers in Bangladesh. Additionally, the findings can help the relevant authorities like the Department of Agriculture Extension (DAE) and Soil Resource Development Institute (SRDI) of Bangladesh to initiate more institutional approaches to equip farmers with the essential knowledge and motivation needed to strengthen their work performance as this will subsequently increase rice production.